Early motor development and co-occurring biomedical conditions in toddlers with Down syndrome - Despradel, Maria, author; Fidler, Deborah, advisor; Graham, James, committee member (Colorado State University. Libraries, 2025)
Down syndrome (DS) is a neurogenetic condition present in 1:800 live births (Bull, 2020). DS is caused by the presence of a third copy of chromosome 21, known as trisomy 21. Trisomy 21 and the overexpression of genes on chromosome 21 are associated with intellectual disability (ID) and a variety of distinct physical characteristics (Bull, 2020). DS is the most common chromosomal cause of ID, typically presenting with mild to moderate severity (National Institute of Child Health and Human Development, 2023). Individuals with DS are also at a higher risk of developing co-occurring biomedical conditions, including congenital heart defects (CHD), neurological disorders, such as infantile spasms and seizure disorders, and vision problems (Bull, 2020). Evidence to date suggests that motor skills are a key area of developmental vulnerability in DS (Sacks & Buckley, 2003). Characterizing early motor skill acquisition in infants with DS is critical to better tailor interventions and therapies to optimize outcomes. This study aims to characterize the range of motor skill presentations within a large sample of infants with DS, and the association between motor skills and co-occurring biomedical conditions.
Department of Human Development and Family Studies.
Department of Occupational Therapy.